Qualidade das águas de chuva em João Pessoa PB: estudo comparativo com padrões de qualidade para uso residencial - Santana, Natalia Cibely Bezerra (2012)
The ever so accelerated population growth in several countries coupled to water resources scarcity have become a crucial problem worldwide. According to the UN, the demand for water is twice as much as that of population growth; so many countries will suffer serious problems of water availability, which will certainly be a challenge for most governments to ensure sufficient supply of drinking water for the population. Among the alternative sources of water supply, one of the most promising is that derived from rainwater collecting; where drinking water is replaced by water which is both less expensive and far more accessible, preserving, therefore, its use where drinkability would not be needed. The purpose of the present research is to analyze the quality of rainwater in the city of João Pessoa and to compare it with several quality standards according to its usages in a residence. Samples were collected at 5 points of the system, namely: direct collection from the atmosphere following water precipitation over roofs; from the first millimeters of precipitation collected from water discarded devices; and from two storage reservoirs. Results revealed that rainwater quality both in its raw state and before its contact with the capturing surface is good; therefore, compatible with the standards established by the NBR's No.15.527/07 and No.13.969/97 (classes 1, 2 and 3), by ANA/05 (class1), and by CONAMA Resolution No.357/05 (class1 of freshwater). Upon flowing over the roof, water quality is deteriorated due to the accumulation of impurities, especially after a dry season. However, it was found that by giving rainwater a simplified treatment, such as simple filtration, or by discarding water from first rains, its quality may be restored up to a satisfactory level, making it compatible to non-potable use, such as in toilet discharge, general cleaning and garden watering. By examining the Ministry of Health Decree No. 2.914/2011, one could verify that the non-conformity alone with the established standards for total and fecal coliforms may render water useless for potable purposes.